Love, Holly : a novel - Stone, Emily, 1989- (Dell Books, 2023)
"Ever since an accident three years ago, Holly has been part of a lonely-hearts letter-writing club for the holidays. The tradition is something she has come to treasure: Each December, she writes to a stranger who is also spending Christmas alone and receives a letter from another lonely person. Usually, the letters go unanswered. That's the point--the letters are anonymous, and the sender writes whatever is in their heart. But this year, the letter Holly receives is different; not only is the letter full of a grief she knows all too well, but its writer, Emma, mentions a place that Holly has visited. When she realizes she might actually be able to find the letter's author, Holly becomes determined to reunite Emma with the estranged grandson, Jack, that she's desperate to reconnect with. And when Holly finally tracks him down, she realizes she's met Jack once before...and the connection was electric. The spark between the two of them is still there--until a misunderstanding risks their burgeoning romance and his strained relationship with Emma, too. But Holly is determined; if she can fix Emma's family, she might also be able to fix her own. Though as it turns out, Holly might have less time to put things right than she thought..."--